Home-based hepatitis C self-testing in people who inject drugs and men who have sex with men in Georgia: a protocol for a randomised controlled trial. Issue 9 (8th September 2022) - Shilton, Sonjelle; Stvilia, Ketevan; Japaridze, Maia; Tsereteli, Nino; Usharidze, Dali; Phevadze, Shota; Jghenti, Miranda; Mozalevskis, Antons; Markby, Jessica; Luhmann, Niklas; Johnson, Cheryl; Nabeta, Pamela; et al.
Abstract : Introduction: Globally, it is estimated that more than three-quarters of people with chronic hepatitis C virus (HCV) are unaware of their HCV status. HCV self-testing (HCVST) may improve access and uptake of HCV testing particularly among key populations such as people who inject drugs (PWID) and men who have sex with men (MSM) where HCV prevalence and incidence are high and barriers to accessing health services due to stigma and discrimination are common. Methods and analysis: This randomised controlled trial compares an online programme offering oral fluid-based HCVST delivered to the home with referral to standard-of-care HCV testing at HCV testing sites. Eligible participants are adults self-identifying as either MSM or PWID who live in Tbilisi or Batumi, Georgia, and whose current HCV status is unknown. Participants will be recruited through an online platform and randomised to one of three arms for MSM (courier delivery, peer delivery and standard-of-care HCV testing (control)) and two for PWID (peer delivery and standard-of-care HCV testing (control)). Participants in the postal delivery group will receive an HCVST kit delivered by an anonymised courier. Participants in the peer delivery groups will schedule delivery of the HCVST by a peer. Control groups will receive information on how to access standard-of-care testing at a testing site. The primary outcome is the number and proportion of participants who report completion of testing. Secondary outcomes include the number and proportion of participants who (a) receive a positive result and are made aware of their status, (b) are referred to and complete HCV RNA confirmatory testing, and (c) start treatment. Acceptability, feasibility, and attitudes around HCV testing and cost will also be evaluated. The target sample size is 1250 participants (250 per arm). Ethics and dissemination: Ethical approval has been obtained from the National Centers for Disease Control and Public Health Georgia Institutional Review Board (IRB) (IRB# 2021-049). Study results will be disseminated by presentations at conferences and via peer-reviewed journals. Protocol version 1.1; 14 July 2021. Trial registration number: ClinicalTrials.gov Registry (NCT04961723 ).